Alginate beads as a carrier for omeprazole/SBA-15 inclusion compound: A step towards the development of personalized paediatric dosage forms. (20th November 2015) - Del Gaudio, Pasquale; De Cicco, Felicetta; Sansone, Francesca; Aquino, Rita Patrizia; Adami, Renata; Ricci, Maurizio; Giovagnoli, Stefano
Graphical abstract: Highlights: Omeprazole/SBA-15 inclusion compound is loaded into alginate beads by prilling. Alginate beads are very consistent in size, drug loading and distribution. Omeprazole release in IF is prolonged in beads with higher alginate concentrations. Formulations may be proposed for the treatment of GERD in paediatric patients. Abstract: The treatment of gastro-esophageal reflux disease (GERD) shows several issues among paediatric patients. This work aims to the formulation of enteric alginate beads loaded with omeprazole (OME) allowing age- and weight-related personalized dosages in children. OME was entrapped in SBA-15 mesoporous compound, characterized and loaded into alginate beads by prilling at different OME and alginate concentrations. The beads resulted of homogeneous size, spherical morphology and very consistent in drug loading and distribution. Formulations demonstrated limited swelling and release (about 10%) in simulated gastric fluid (SGF) after 2 h and a prolonged release in simulated intestinal fluid (SIF), till 6 h, due to a mixed diffusion-case II transport mechanism. The beads were superior to the market product, which showed lower release in SGF but immediate dissolution in SIF. The high alginate beads uniformity and release properties make them a potential novel tool for a personalized treatment of GERD in children.